Satisfaction with sex life and its impact on the quality of life in people living with HIV in Poland treated in the city of Bialystok: a cross-sectional study - Milewska-Buzun, Marta; Cybulski, Mateusz; Baranowska, Anna; Krajewska-Kułak, Elżbieta; Kózka, Maria; Paradowska-Stankiewicz, Iwona (Frontiers in Psychiatry, 2023)
Introduction: Sex life is an important element contributing to the overall quality of life. It is also a particularly sensitive dimension of quality of life for HIV-positive patients. Objective: The aim of the study was to assess the sexual life of people living with HIV in Poland treated in the Observation and Infection Clinic with the Subunit for HIV/AIDS Patients of the University Clinical Hospital in Bialystok, and its impact on the quality of life, life satisfaction, HIV status acceptance, general health status and depressive symptoms among the respondents. Methods: A total of 147 participants, including 104 men (70.7%) and 43 women (29.3%), took part in the research. The study was conducted between May 2019 and January 2020. The study used a diagnostic survey method with a modified questionnaire "Psychosocial situation of people living with HIV/AIDS" by Dr Magdalena Ankiersztejn-Bartczak and the following standardised psychometric tools: The World Health Organization Quality of Life (WHOQOL-BREF), Short Form Health Survey (SF-36), Acceptance of Illness Scale (AIS), Satisfaction with Life Scale (SWLS), General Health Questionnaire (GHQ-28) and Beck Depression Inventory (BDI). Results: One-third of patients rated their sex life as poor or very poor. Almost half of respondents always informed sexual partners of their HIV status (49.7%). The sex life of respondents was highly correlated with almost all psychometric measures used in the study. Those indicating sexual contact as a possible source of HIV infection had a lower quality of life in the domain of general health compared to other respondents, but the difference was relatively small (about 5.5 points). Discussion: In conclusion, the overall satisfaction with the sex life of people living with HIV was moderate with a tendency to poor. The quality of life of people living with HIV was determined by their sex life. Better quality of life was presented by those with good self-reported sex life.